Prosocial Behavior Based On Culture, Social Economic Conditions, And Gender - Syaiful Indra; Hasta Purna Putra; Eko Sujadi (Program Studi Bimbingan dan Konseling FKIP UMSU, 2021)
Prosocial behavior is a voluntary act actualized in the attitude of getting rid of personal interests in providing benefits to other individuals. This study aims to analyze: To find out the description of prosocial behavior, to find out differences in prosocial behavior in terms of socio-economic conditions, to find out differences in students' prosocial behavior in terms of gender, to find out differences in students' prosocial behavior in terms of culture, and to find out differences in students' prosocial behavior. in terms of the interaction between culture, socio-economic conditions, gender. This type of research is a descriptive comparative research that uses comparative analysis techniques. The population of this research is the students of SMP Islam Hands as many as 123 people. The students who were used as samples in this study were 123 people. The instrument used is a Likert scale. Hypothesis testing in research to see differences in prosocial behavior in terms of socioeconomic status, gender and majors will use a three-way Analysis of Variance (ANOVA).